Out of the ashes - Morpurgo, Michael; Foreman, Michael (Macmillan Children's London, 2012)
When foot and mouth disease breaks out on a pig farm hundreds of miles from Becky Morley's Devon home, no one believes it will spread very far. But now the nightmare is a few fields away. Local sheep are infected and every animal is immediately destroyed. Will the Morley's flock be next?